Duganella dendranthematis sp. nov. and Massilia forsythiae sp. nov., isolated from flowers. Issue 8 (16th August 2022) - Heo, Jun; Won, Miyoung; Lee, Daseul; Han, Byeong-Hak; Hong, Seung-Beom; Kwon, Soon-Wo
Abstract : Two aerobic, Gram-stain-negative, motile, mesophilic, rod-shaped and catalase-positive bacterial strains designated AF9R3 T and GN2-R2 T were isolated from flowers collected in the Republic of Korea. Strain AF9R3 T grew at 4–33 °C, pH 4.0–9.0 and with 0–1 % NaCl (w/v), and strain GN2-R2 T grew at 10–33 °C, pH 4.0–9.0 and with 0–1 % NaCl (w/v). Phylogenetic analysis on the basis of 16S rRNA gene sequences indicated that strains AF9R3 T and GN2-R2 T belonged to the genera Duganella and Massilia, respectively, showing high sequence similarity to Duganella levis CY42W T (99.4 %) and Massilia putida 6 NM-7 T (98.0 %), respectively. Both strains contained summed feature 3 (C16 : 1  ω 7 c and/or C16 : 1  ω 6 c ) and C16 : 0 as the major fatty acids, and ubiquinone Q-8 as the predominant quinone. Strain AF9R3 T had diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine, and strain GN2-R2 T comprised diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and an unidentified phospholipid as the major polar lipids. Orthologous average nucleotide identity and digital DNA–DNA hybridization values of strain AF9R3 T to its closest relative D. levis CY42W T were 92.6 and 56.5 %, and those of strain GN2-R2 T to its closest relative M. putida 6 NM-7 T were 81.4 and 24.8 %. Based on genotypic and phenotypic data, strains AF9R3 T and GN2-R2 T are considered to represent novel species of the genus Duganella and Massilia, respectively, for which the names Duganella dendranthematis sp. nov. (type strain AF9R3 T =KACC 21258 T =NBRC 114510 T ) and Massilia forsythiae sp. nov. (type strain GN2-R2 T =KACC 21261 T =NBRC 114511 T ) have been proposed.